2021
DOI: 10.1108/tqm-11-2020-0269
|View full text |Cite
|
Sign up to set email alerts
|

The soft side of TQM and teachers job satisfaction: an empirical investigation in primary and secondary education

Abstract: PurposeThe current study provides insights on the application of critical soft TQM practices in primary and secondary education and their impact on teachers' job satisfaction (TJS).Design/methodology/approachBased on a review of the literature related to TQM application in primary and secondary education, six soft TQM elements were traced as critical to the success of TQM implementation in the school environment: participation/involvement in continuous improvement, teamwork, empowerment, appraisal systems/reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 46 publications
2
33
0
1
Order By: Relevance
“…In particular, training contributes to increasing employees' readiness to change and resilience, which are conducive to a commitment to organizational excellence (Lasrado, 2016). Furthermore, it leads to an organizational culture supportive of a TQM approach (Glaveli et al, 2021), facilitating knowledge development for the purpose of quality improvement (Nikbakht et al, 2012). Motivation propels commitment to organizational excellence at the individual and collective levels (Ghafoor et al, 2011).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In particular, training contributes to increasing employees' readiness to change and resilience, which are conducive to a commitment to organizational excellence (Lasrado, 2016). Furthermore, it leads to an organizational culture supportive of a TQM approach (Glaveli et al, 2021), facilitating knowledge development for the purpose of quality improvement (Nikbakht et al, 2012). Motivation propels commitment to organizational excellence at the individual and collective levels (Ghafoor et al, 2011).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In addition, the latest study (Ahmed & Idris, 2021)gives the result that is TQM has a significant effect on job satisfaction, especially on the TQM sub-variable empowerment of employees with the highest correlation compared to the TQM sub-variable. The results of the study (Glaveli et al, 2021) show the same thing where TQM affects teacher job satisfaction, which can also be concluded that quality improvement especially in schools is important to improve.…”
Section: Introduction *mentioning
confidence: 55%
“…The study (Glaveli et al, 2021) found leadership and empowerment were the most widely applied TQM practices. In addition, involvement, the assessment system, reward, and leadership are elements of TQM that have a positive relationship with teacher job satisfaction.…”
Section: Total Quality Management (Tqm)mentioning
confidence: 94%